2000
DOI: 10.1177/107327480000700201
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of Cancer Pain

Abstract: Understanding the neurophysiology of cancer pain promotes use of the most appropriate palliative measures for pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 60 publications
1
35
0
2
Order By: Relevance
“…61,70 NCP can arise as a consequence of cancer-directed therapy, such as surgery, radiotherapy and chemotherapy (treatment-related therapy). 7,[71][72][73][74][75] Treatment adverse effects include joint pain following chemotherapy and hormonal therapy and/or painful mucositis due to radiotherapy and chemotherapy with certain agents. It has been widely reported that drugs such as paclitaxel, vincristine, cisplatin and bortezomib may produce sensory neuropathies.…”
Section: 49mentioning
confidence: 99%
See 2 more Smart Citations
“…61,70 NCP can arise as a consequence of cancer-directed therapy, such as surgery, radiotherapy and chemotherapy (treatment-related therapy). 7,[71][72][73][74][75] Treatment adverse effects include joint pain following chemotherapy and hormonal therapy and/or painful mucositis due to radiotherapy and chemotherapy with certain agents. It has been widely reported that drugs such as paclitaxel, vincristine, cisplatin and bortezomib may produce sensory neuropathies.…”
Section: 49mentioning
confidence: 99%
“…Some of the mechanisms contributing to CIBP include periosteum stretching by tumor expansion, bony distortion by local microfractures, nerve compression due to collapsed vertebrae or direct tumor encroachment, and algesic substances local release from the bone marrow. 23,72,81,82 CIBP perhaps best illustrates the complexity of malignancies, clinically demonstrating a hallmark of cancer pain, with presence of painless disease at some sites and severely painful at others. 7 Bone pain has been correlated with osteoclastic activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathic cancer pain is caused by peripheral or central nervous system damage due to released inflammatory cytokines that sensitize neurons. [37] Carcinoma-induced pain is not related to tumor size and small carcinomas produce severe pain. [6] These observations suggest that carcinoma pain is primarily of neuropathic origin and is characterized by mechanical hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Although this information holds promise for the development of new therapies for cancer pain, blocking these mediators individually is not sufficient to block cancer pain completely, indicating that tumor-induced pain is produced by multifaceted mechanisms. Several recent reviews 28,40,60,61,70,[101][102][103][104]114,137,145,169,170,183 focus on the mechanisms of cancer pain and the mediators involved, and the reader is referred to these excellent sources for more complete summaries of this information.…”
mentioning
confidence: 99%